ANALISIS INVENTARISASI ASET BERGERAK BERDASARKAN PERMENDAGRI NOMOR 47 TAHUN 2021 PADA DINAS KOPERASI USAHA KECIL DAN MENENGAH DAN PERDAGANGAN KOTA SURABAYA - Azizah Rahmania; Wahyu Millensyah Erwing (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to evaluate the implementation of movable asset inventory at the Office of Cooperatives, Small and Medium Enterprises, and Trade of Surabaya City and to assess its compliance with Regulation of the Minister of Home Affairs Number 47 of 2021. The research adopts a qualitative descriptive approach, with data collected through non-participant observation and analysis of inventory-related documents, including work procedures, asset records, and asset security guidelines. The findings indicate that, from a theoretical and normative perspective, the inventory process has followed the required stages of preparation, implementation, reporting, and follow-up in accordance with applicable regulations. However, in practice, several shortcomings remain, particularly in technical and administrative aspects, such as inconsistencies in recording and less-than-optimal supporting documentation. Therefore, consistency and diligence in applying inventory procedures are essential elements in achieving orderly, accurate, and accountable regional asset management.